2011
DOI: 10.1042/bj20110512
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in BACE1 decreases body weight, protects against diet-induced obesity and enhances insulin sensitivity in mice

Abstract: Insulin resistance and impaired glucose homoeostasis are important indicators of Type 2 diabetes and are early risk factors of AD (Alzheimer's disease). An essential feature of AD pathology is the presence of BACE1 (β-site amyloid precursor protein-cleaving enzyme 1), which regulates production of toxic amyloid peptides. However, whether BACE1 also plays a role in glucose homoeostasis is presently unknown. We have used transgenic mice to analyse the effects of loss of BACE1 on body weight, and lipid and glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
119
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(133 citation statements)
references
References 50 publications
13
119
0
1
Order By: Relevance
“…There are also concerns about potential on-target side effects of BACE1 inhibition due to the large number of BACE1 substrates that the enzyme is believed to cleave (Hemming et al 2009;Kuhn et al 2012). While numerous investigators have described BACE1 knockout (KO) mice as being viable, fertile, and with no gross or histological abnormalities (Luo et al 2001(Luo et al , 2003Roberds et al 2001), others have reported effects on growth and mortality, adiposity, hypomyelination, schizophrenia-like behavior, seizures, and defects in cognition and motor coordination (Laird et al 2005;Dominguez et al 2005;Willem et al 2006;Savonenko et al 2008;Hu et al 2010;Meakin et al 2012;Cheret et al 2013). The long-term effects of pharmacological inhibition of BACE1 in animals or humans have not been reported; however, latestage clinical studies are underway.…”
Section: Introductionmentioning
confidence: 99%
“…There are also concerns about potential on-target side effects of BACE1 inhibition due to the large number of BACE1 substrates that the enzyme is believed to cleave (Hemming et al 2009;Kuhn et al 2012). While numerous investigators have described BACE1 knockout (KO) mice as being viable, fertile, and with no gross or histological abnormalities (Luo et al 2001(Luo et al , 2003Roberds et al 2001), others have reported effects on growth and mortality, adiposity, hypomyelination, schizophrenia-like behavior, seizures, and defects in cognition and motor coordination (Laird et al 2005;Dominguez et al 2005;Willem et al 2006;Savonenko et al 2008;Hu et al 2010;Meakin et al 2012;Cheret et al 2013). The long-term effects of pharmacological inhibition of BACE1 in animals or humans have not been reported; however, latestage clinical studies are underway.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, BACE1 finsertms to play a role in glucose and lipid homoeostasis and may be a link between Alzheimer's disease and diabetes [19,20]. Besides its well-characterized expression pattern in the brain, BACE1 mRNA was also detected in non-neuronal tissue, especially within the pancreas [21,22].…”
Section: Discussionmentioning
confidence: 93%
“…203 Pharmacological reduction of BACE1 activity by Merck-3 inhibitor in a skeletal muscle cell line also increased insulin signaling and glucose uptake. 203 These results suggest a role for BACE1 in glucose homoeostasis, which is further supported by proteomics studies. 101 As type 2 diabetes is being proposed as a possible risk factor for AD, 204 determining if BACE1 inhibition may help fight insulin resistance and decrease blood glucose levels would require future interest.…”
mentioning
confidence: 97%
“…Interestingly, the close observation of BACE1 -/-mice showed a reduction in body weight, with increased energy expenditure and reduced metabolic efficiency, as well as increased glucose disposal and insulin sensitivity. 203 These mice are also protected against high fat diet-induced obesity. 203 Pharmacological reduction of BACE1 activity by Merck-3 inhibitor in a skeletal muscle cell line also increased insulin signaling and glucose uptake.…”
mentioning
confidence: 97%
See 1 more Smart Citation